2021
DOI: 10.3390/md19020096
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Inhibitory Effect of (−)-loliolide Isolated from Sargassum horneri in 3T3-L1 Adipocytes: Inhibitory Mechanism of Adipose-Specific Proteins

Abstract: Sargassum horneri (S. horneri) is a well-known brown seaweed widely distributed worldwide. Several biological activities of S. horneri have been reported. However, its effects on lipid metabolism and the underlying mechanisms remain elusive. In the present study, we examined the inhibitory effect of the active compound “(−)-loliolide ((6S,7aR)-6-hydroxy-4,4,7a-trimethyl-5,6,7,7a-tetrahydro-1-benzofuran-2(4H)-one (HTT))” from S. horneri extract on lipid accumulation in differentiated adipocytes. MTT assays demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…We found that the S. horneri water extract component enhanced the insulin-stimulated differentiation of bone marrow stem cells into osteoblasts and suppressed the formation of adipocytes [35]. S. horneri extract also has inhibitory effects on lipid metabolism in 3T3-L1 adipocytes in vitro [36]. Thus, the S. horneri component may have the effect of suppressing the differentiation of bone marrow cells into adipocytes.…”
Section: S Horneri Extract Component Suppresses Adipogenesis In Bone ...mentioning
confidence: 74%
“…We found that the S. horneri water extract component enhanced the insulin-stimulated differentiation of bone marrow stem cells into osteoblasts and suppressed the formation of adipocytes [35]. S. horneri extract also has inhibitory effects on lipid metabolism in 3T3-L1 adipocytes in vitro [36]. Thus, the S. horneri component may have the effect of suppressing the differentiation of bone marrow cells into adipocytes.…”
Section: S Horneri Extract Component Suppresses Adipogenesis In Bone ...mentioning
confidence: 74%
“…Cinnamic acid, detected in both samples, interestingly showed in vivo anti-obesity activity in high fat diet-fed rats [48]. The monoterpene lactone loliolide was demonstrated to significantly reduce the intracellular lipid accumulation in 3T3-L1 adipocytes [49].…”
Section: In Vitro Pancreatic Lipase Inhibitionmentioning
confidence: 91%
“…Thus, this cell line is a suitable screening model for obesity-related adipose tissue biology. Some natural products and plant extracts, such as Abelmoschus manihot [12], Albizia julibrissin [13], Amomum tsao-ko [14], indole derivatives [15], (−)loliolide [16], kaempferol [17], Salix pseudolasiogyne [18], and shrimp oil [19], are known to prevent the lipid accumulation or the differentiation of adipocytes in 3T3-L1 cells.…”
Section: Introductionmentioning
confidence: 99%
“…In our present research, we conducted investigations to identify potential bioactive phytochemicals in the ethyl acetate (EtOAc) and methylene chloride (CH 2 Cl 2 ) fraction of the S. sieboldii EtOH extract. We included chromatographic purification and structural identification of one undescribed α-hydroxy acid derivative (16) and two new lanostane-type triterpenoids (17 and 18), which were isolated along with additional known constituents (1-15 and 19). The structure of the novel constituents was characterized using various spectral experiments (1D/2D NMR and HR-MS) and specific optical rotation analyses.…”
Section: Introductionmentioning
confidence: 99%